2013
DOI: 10.1186/1556-276x-8-80
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of high-density Pt nanodots on Al2O3 film using (MeCp)Pt(Me)3 and O2 precursors for nonvolatile memory applications

Abstract: Pt nanodots have been grown on Al2O3 film via atomic layer deposition (ALD) using (MeCp)Pt(Me)3 and O2 precursors. Influence of the substrate temperature, pulse time of (MeCp)Pt(Me)3, and deposition cycles on ALD Pt has been studied comprehensively by scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. Therefore, Pt nanodots with a high density of approximately 2 × 1012 cm-2 have been achieved under optimized conditions: 300°C substrate temperature, 1 s pulse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 22 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…Overexpression of two Arabidopsis AP2/EREBP genes, CBF1 and DREB1A, resulted in stronger tolerance to drought, salt, and freezing [24] [26] . Transgenic Arabidopsis plants overexpressing CBF3 under the control of cauliflower mosaic virus (CaMV) 35S promoter also showed a high tolerance to drought, high-salinity, and freezing stress [25] , [27] , [28] . Five CBF and AP2/EREBP genes were highly expressed in SM as compared to SMT.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of two Arabidopsis AP2/EREBP genes, CBF1 and DREB1A, resulted in stronger tolerance to drought, salt, and freezing [24] [26] . Transgenic Arabidopsis plants overexpressing CBF3 under the control of cauliflower mosaic virus (CaMV) 35S promoter also showed a high tolerance to drought, high-salinity, and freezing stress [25] , [27] , [28] . Five CBF and AP2/EREBP genes were highly expressed in SM as compared to SMT.…”
Section: Discussionmentioning
confidence: 99%
“…A number of processes have been studied for NVM device applications but these processes do not ensure size control of QDs below 2 nm with good uniformity. A few of such processes like sputtering [8] and atomic layer deposition (ALD) [9] for Pt nanocrystals, ion beam synthesis is utilised for GaN and silicon QDs synthesis [10], e‐beam evaporation and annealing for Co [11] and many more. Even, most of these processes require complex and costly infrastructure for nanocrystals/QDs synthesis; whereas, by colloidal synthesis, the size of below 2 nm of Co QDs could be achieved with uniform size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the technique of atomic layer deposition (ALD), which is based on sequential self-limited and complementary surface chemisorption reactions, has been considered as a perfect thin film deposition method because of its outstanding advantages such as relatively low process temperature, stoichiometric composition, large-area uniformity, precise thickness control, and high conformability [ 13 , 14 ]. Furthermore, ALD is also a very promising method for preparing high-density metal NPs (e.g., Pt, Ir, and Ru) at relatively low temperature of <350 °C [ 15 17 ]. As an example, Liu et al obtained Ir NPs with a high density of 0.6 × 10 12 cm −2 and an average size of 4.9 nm by ALD at 300 °C for nonvolatile memory applications [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Liu et al obtained Ir NPs with a high density of 0.6 × 10 12 cm −2 and an average size of 4.9 nm by ALD at 300 °C for nonvolatile memory applications [ 17 ]. Ding et al also reported that two-dimensional high-density Pt NPs (2 × 10 12 cm −2 ) were self-assembled on the Al 2 O 3 film at 300 °C by ALD, which demonstrated noticeable electron trapping capacity in Si-based nonvolatile memory [ 15 ].…”
Section: Introductionmentioning
confidence: 99%